What lies ahead: 12 predictions for 2017. Issue 3 (December 2016) - Colebrook, Catherine; Gardiner, Laura; Kelly, Gavin; Griffiths, Rita; Gildea, Robert; Glennie, Alex; Torfeh, Massoumeh; de Vos, Pierre; Breimaier, Silke; Taylor, Matthew; Murray, Chris; Fakih, Bissan
Abstract : 2016 blows other recent years out of the water for political, economic, social and environmental turbulence. Amid an apparently bleak landscape of rising nationalism, a refugee crisis, continued war and terrorism, and the warmest year on record, can any of our leading commentators see a glimmer of light ahead?